Study on Relationship Between the Nutritional Status and Dental Caries in 8-12 Year Old Children of Udaipur City, India - Panwar, NK; Mohan, M; Arora, R; Gupta, A; Marya, CM; Dhingria, S (Kathmandu University Medical Journal, 2015)
Background The future health of individuals depends on the well being of the children of today. Proper nutrition for children is very important. The most commonly used index of obesity and over weight is Body Mass Index. The growth of children should be monitored using the Body Mass Index (BMI) and risk factors assessed through a dietary and physical activity history. The increase in obesity is attributed to increased carbohydrate consumption among children. Obesity and caries are both diet-based conditions that share a cause that is, excessive ingestion of fermentable carbohydrates.Objective This study was undertaken to determine the association of nutritional status with dental caries in 8 to 12 year old children of Udaipur city.Method The present study was conducted on a random sample of 1000 boys and girls, aged 8-12 years. The children were selected from schools located in the Udaipur City, Rajasthan. The schools examined were of government and private sector schools in Udaipur city. The children from schools of Udaipur city was taken in the study with male, female and age group ratio as per distribution in population. A proforma was used to record children’s age, gender, school, year, height, weight, parental income and dental caries status. Statistical analysis was done using Statistical Package of Social Science (SPSS Version 15; Chicago Inc., USA).Result It was found that caries free individuals were more from normal nutritional status group with 134 (13.4 %) subjects where as only 11 (1.1 %) of subjects obese children were found caries free.Conclusion Study shows that the children with normal BMI for age had more caries in their primary teeth, as well as in their permanent teeth, than the overweight children.Kathmandu University Medical Journal Vol.12(1) 2014: 26-31